Projeto de um sistema emulador de escoamentos e vaso de separação primária - Vieira, Plínio Altoé Costa (2009)
The purpose of this study was to develop a pilot plant which the main goal is to emulate a flow peak pressure in a separation vessel. Effect similar that is caused by the production in a slug flow in production wells equipped with the artificial lift method plunger lift. The motivation for its development was the need to test in a plant on a smaller scale, a new technique developed to estimate the gas flow in production wells equipped with plunger lift. To develop it, studies about multiphase flow effects, operation methods of artificial lift in plunger lift wells, industrial instrumentation elements, control valves, vessel sizing separators and measurement systems were done. The methodology used was the definition of process flowcharts, its parameters and how the effects needed would be generated for the success of the experiments. Therefore, control valves, the design and construction of vessels and the acquisition of other equipment used were defined. One of the vessels works as a tank of compressed air that is connected to the separation vessel and generates pulses of gas controlled by a on/off valve. With the emulator system ready, several control experiments were made, being the control of peak flow pressure generation and the flow meter the main experiments, this way, it was confirmed the efficiency of the plant usage in the problem that motivated it. It was concluded that the system is capable of generate effects of flow with peak pressure in a primary separation vessel. Studies such as the estimation of gas flow at the exit of the vessel and several academic studies can be done and tested on a smaller scale and then applied in real plants, avoiding waste of time and money.